Resilience strategies of West African pastoralists in response to scarce forage resources - Ouédraogo, Karim; Zaré, Alhassane; Korbéogo, Gabin (Springer, 2021)
Finding sufficient natural fodder resources to feed livestock has become a challenge for herders in the Sahel zone of Burkina Faso. Despite the existence of pastoral reserves, the issue of fodder shortage remains unsolved. This article highlights the changes in behaviour and the evolution of pastoral practices caused by the scarcity of forage resources. These changes are defined and classified as resilience strategies. Thus, this paper aims to analyse these strategies using new semantics that calls for other forms of perceptions or approach to the questions of pastoralists’ resilience strategies. Interviews (semi-structured and casual conversations), ethnographic observations and ethnobotanical surveys were used to collect data. In rangelands, such high value fodder species as Andropogon gayanus, Pennisetum pedicellatum and Dactyloctenium aegyptium that were abundant herbaceous plants during the last decades are disappearing. Concomitantly, species with lower forage value, such as Senna obtusifolia, which are more resilient to ecological disturbance factors, are colonizing rangelands. Faced with these ecological changes, pastoralists are trying to redefine and reconfigure their practices, and this implies a redefinition of their identity. They use resilience strategies such as mowing grasses, building up fodder bundles, conserving crop residues exploiting Senna obtusifolia (a previously neglected species), using woody fodder and adapting the type of livestock and the size of the herds to the ability of pastoralists to feed them. Strategies that are older than these are the integration of agriculture with livestock and decollectivized transhumance. It is these resilience strategies that this article exposes and analyses as defence mechanisms of Sahelian pastoralists in the face of the depletion of forage resources in their environments.
Pastoralism, 11(1), 16.
Keywords: Oumarou Ouédraogo; Anja Linstädter; CEFORGRIS; Université Joseph Ki-Zerbo; Burkina Faso; Ecological changes; Forage values; Pastoralism